PERBANDINGAN KOMPETENSI BIOLOGI SISWA XI MIA ANTARA MODEL PEMBELAJARAN GUIDED DISCOVERY LEARNING DAN PROBLEM BASED LEARNING PADA MATERI SISTEM PENCERNAAN DI SMAN 1 SUNGAI TARAB - Handayani, Delsi Fitri; Advinda, Linda; Anhar, Azwir (Kolaboratif, 2015)
Biology competence of students grade XI science in senior high school 1 Sungai Tarab is still low because the teacher has not used an apropriate learning model 2013 curriculum-based yet. It makes students felt difficult to understand the concept, less-motivated, less active in the class, shy to ask, and give opinion. The characteristics of the topic should be considered in choosing a model which suits to the concept and princip of the topic. Based on the overview on the characteristics of the topic, Guided Discovery Learning an Problem Based Learning models can be used in teaching and learning processes. Therefore, this research is conducted related to the comperative study of biology competence of XI MIA students between Guided Discovery Learning and Problem Based Learning models in the topic of digestion system. The purpose of this reseach is to find differences between biology competence of the students who use Guided Discovery Learning model and the ones who use Problem Based Learning model in the topic of digestion system in senior high school 1 Sungai Tarab students grade XI science the academic year 2014/2015 Type of the research was quasi experimental research with The Static Group Comparison design. The population was three classes of the XI MIA senior high school 1 Sungai Tarab in the academic Year 2014/2015 and the sample which using Purposive Sampling technique was XI MIA2 as the first experimental class and XI MIA3 as the second experimental class. Instruments used were objective test and observation sheet. Data analysis used was t test with criteria: if tcount>ttable, hypothesis was accepted and vice versa (cognitive aspect), and u test with criteria: if Zcount>Ztable, hypothesis was accepted and vice versa (affective and psychomotor aspect). Data analysis of cognitive aspect in a significant rate (α) = 0,05 with dk 37 was tcount= 3, 0749 >ttable= 1, 6905, the hypothesis was accepted. So did affective and psychomotor aspect, Zcount= 1, 756>Ztable= 1, 6905 (affective) and Zcount= 1,8820>Ztable= 1, 6905 (psychomotor), the hypothesis was accepted. The results indicated that the students’ biology competency were significantly different between Guided Discovery Learning and Problem Based Learning model. Students’ biology competency using Problem Based Learning model was better than Guided Discovery Learning model.